Exploring Faculty Members Perspective on the Implementation of Take-home assessments in Medical Education during the COVID-19 Outbreak: A Qualitative study - Abtin Heidarzadeh; Samaneh Beik; Hanieh Hashemi; Parvane Parvasideh (Mashhad University of Medical Sciences, 2022)
Background: In early 2020, due to COVID-19, public lockdowns challenged the academic community by conducting a wide range of remote exams. The current study planned to survey the faculty member's perspective on the challenges and the solution approach ahead of this sudden transmission and the feasible medical educational assessments conducted in an online Take-home format.Methods: The current paper was a cross-sectional and descriptive study. We collected data through an online interview form consisting of close-ended and open-ended questions completed by Iranian universities of medical sciences teachers. We analyzed the received data using descriptive, inferential statistics and a thematic analysis approach through SPSS25 and MAXQDA2020 software.Results: A total of 574 medical teachers enrolled in our survey. Midterm university exams and internal-university language tests were selected, by responders, as a suitable option for holding online assessments. Other summative or sensitive assessments were not eligible to use this process. We also extracted 640 codes related to challenges and solution approaches. The significant difficulties were the problems in the executive infrastructure (124codes), and improving the implementation of online testing (84 codes) was considered the best feasible solution in teachers' perceptions.Conclusion: The results showed that teachers believed that high-stake tests, according to the current technical and cultural infrastructure, are not far from the mind and access. Still, there is a critical need to explore more to provide a stable and reliable online exams environment.